Investing in Real Estate: Mortgage Financing Practices and Optimal Holding Period - KOH, Winston T. H. (Institutional Knowledge at Singapore Management University, 2005)
Real estate investments are typically characterized by high degrees of leverage and long loan tenures. In perfect capital markets, leverage has no impact on the investment decision apart from tax considerations. However, the mortgage financing market is imperfect in many countries. In the presence of market imperfections, an optimal holding period exists for real property investments. We provide a simple rule to calculate the optimal holding period is to compare the required rate of return with the leveraged rate of return on equity.